The Effect of Information Literacy on Students’ Information Overload in the Use of Digital Academic References - Dea Olivia; Desriyeni Desriyeni (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
This study is motivated by the increasing volume of digital information that may lead to information overload among students, particularly when using digital academic references. The main problem addressed in this research is students’ limited ability to select, evaluate, and effectively use information amid the abundance of available sources. This study aims to analyze the effect of information literacy on students’ information overload in the use of digital academic references. A quantitative approach with a descriptive survey design was employed. The population consisted of students from the Library and Information Science Program at Universitas Negeri Padang from the 2023–2025 cohorts, with a total sample of 73 respondents selected using proportionate stratified random sampling. Data were collected through questionnaires and preliminary interviews and analyzed using descriptive statistics and simple linear regression. The findings indicate that information literacy has a significant effect on information overload, with a significance value of p < .001 and a t-value of 5.611. The coefficient of determination of 30.7% shows that information literacy contributes to students’ ability to manage information overload. These findings suggest that higher levels of information literacy enhance students’ capacity to select, evaluate, and use digital academic references effectively, thereby minimizing the risk of information overload. This study contributes to the literature on information literacy and digital academic behavior by providing empirical evidence of the role of information literacy in managing excessive information exposure. Practically, the findings imply the need to strengthen information literacy programs in higher education to improve students’ critical and effective use of digital academic references.